The Influence of Psychological Empowerment on the Affective Commitment of Millennial Workers - Muchtadin Muchtadin (MAR-Ekonomi: Jurnal Manajemen, Akuntansi Dan Rumpun Ilmu Ekonomi, 2024)
The millennial generation has its own characteristics compared to other generations. Millennials tend not to feel connected to their work. The research aims to determine the influence that dimensions of psychological empowerment such as meaning, competence, self-determination and impact have on the affective commitment of millennial workers. Respondents were 100 millennial workers in Indonesia who were selected using convenience sampling. Respondents were born between 1981 and 1996. The data analysis method used was PLS SEM. The research results found that the dimensions of meaning and impact had a positive effect on affective commitment, while competence and self-determination had no effect on affective commitment. This research contributes to increasing affective commitment through psychological empowerment among millennial workers in Indonesia.